(untitled) (Journal of actual problems of jurisprudence, 2018)
The article analyzes scientific-theoretical and legal definitions of the administrative and legal regimes and gives their main features, characteristics and classification. Special attention is given to the regimes military and emergency states as well as emergency situation of social character, their characteristic features are defined. Key words: legal regimes, administrative and legal regime, legal regulation, state of emergency, military emergency, emergency situation of social character.